ANNOTATED CHECKLIST AND KEY FOR SMUT FUNGI IN COLOMBIA - PIEPENBRING M. (Caldasia)
71 species of smut fungi known for Colombia are cited in a checklist together with their host plants, collection data, and some comments. 20 species of smut fungi are reported for the first time for Colombia. The list includes the new species Aurantiosporium colombianum and the new combination Sporisorium concelatum. Ustilago garcesi is recognized as a synonym of Sporisorium panici-leucophaei. Four species of host plants were not yet known to be infected by the respective smut species. The smuts known for Colombia are presented in a key which contains distinctive characteristics of sori and spores.